Time-use and mental health in older adults: a scoping review - Foong, Hui Foh; Lim, Sook Yee; Koris, Roshanim; Haron, Sharifah Azizah (MDPI, 2021)
Time-use of older adults can be different than in earlier life, especially during the transition from pre- to post-retirement or after experiencing major life events, and the changes could affect their mental health. However, the extent and nature of such research in gerontology have not been examined to date. Therefore, this scoping review sought to map the literature on time-use and mental health in the older population to examine the extent and nature of those research activities. A scoping review was conducted using four databases—PubMed, Scopus, CINAHL, and EMBASE according to PRISMA guidelines. Data were extracted using a pretested tool to develop a descriptive analysis and thematic summary. A total of 11 articles met the eligibility criteria. Seven out of 11 studies involved cross-sectional design, while the remainder were longitudinal studies. The longitudinal studies mainly were secondary data analysis. Time-use data were mainly collected using daily diaries, and the most common mental health outcome included was depression. Only two studies did not evaluate the direct relationship between time-use and mental health. Our review has revealed studies evaluating time-use and mental health in older adults. Limitations of review and recommendations for future studies are discussed.